PEMBENTUKAN KARAKTER KEMANDIRIAN MELALUI KEGIATAN OSIS DI SEKOLAH MENENGAH ATAS - Japar, Muhammad; Parida, Desca (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2018)
This study aims to determine character independence building of senior high school students through the activities of OSIS in SMA Negeri 42 Jakarta. SMA Negeri 42 Jakarta is one of the schools that implements character education, especially the character of independence. The research method used is qualitative. The data was conducted by observation, documentation, and interviews to informants and key informant in SMA Negeri 42 Jakarta. The Interview conducted to the board of OSIS by using purposive sampling method. And by adding two key informant that is coach and student council Vice Head of Student Affairs. After that it is equipped by expert opinion. The results showed that the activities performed by OSIS SMA Negeri 42 Jakarta in shaping the character of OSIS management included viewing, speaking and listening activities, writing activities, moving activities, mental activities, and soul movement activities. Implementation of character-based self-reliant education conducted on board of OSIS includes the guidance of independence from the aspect of emotional independence, independence, economy, intellectual independence, and social independence. These activities are reflected by planning, implementing and evaluating each activity fairly well and upholding the spirit of mutual cooperation